FINANCIAL PERFORMANCE ANALYSIS OF BANK SYARIAH INDONESIA THROUGH CAMEL APPROACH FROM 2019 - 2021 - Sarif, Akbar; Ariyanti, Rini (Journal Of Islamic Ekonomic and Business, 2023)
The bank's financial performance describes the financial condition in a certain period involving aspects of raising funds and channeling funds as measured by indicators of capital adequacy, liquidity, and bank profitability. The CAMEL method is used as an assessment of the level of performance and soundness of an operating bank to serve as a reference for the smooth operation of the bank. These aspects include Capital (capital adequacy), Asset Quality (asset quality), Management (management), and Earnings (profitability). , and Liquidity (liquidity). In this journal, financial performance will be judged by its financial ratios NPF (Non-Performing Financing), FDR (Financing to Deposit Ratio), ROA (Return on Assets), ROE (Return on Equity), NIM (Net Interest Margin), CAR (Capital Adequacy Ratio). Having a financial performance report is very useful for a company as a basis for determining the company's strategy for the future. Looking at the company's overall performance, can even guide in making decisions.